Study of craniofacial skeletal patterns and body measurements in south Indians - Prabhu, Suchitra S; Avadhani, Ramakrishna; Mascarenhas, Rohan; Neela, Praveen Kumar (International Multidisciplinary Research Journal, 2013)
Introduction:Craniofacial skeletal pattern and body measurements have been studied in anthropology, orthodontics, cosmetology and garment industries. The purpose of this study was to find the relationship between craniofacial skeletal pattern and body measurements, Ratios and BMI. Methods: Digital lateral cephalogram was recorded for all the two hundred subjects and were traced and analysed using six cephalometric measurements to identify craniofacial skeletal pattern. These two hundred subjects were divided into three groups Vertical, Horizontal and Average. Then twenty five subjects from each group were randomly selected for this study. Each subject’s height, weight, chest, waist and hip were measured and the ratios and BMI were derived. Data was tabulated and statistically analysed. Results: Waist measurement showed significant difference between Vertical and Horizontal groups. The body mass index showed significant differences between Vertical and Average group. However, there were no significant differences in any measurements taken between Horizontal and Average. Conclusion: The data recorded by the present study shows that waist and BMI are significantly associated with each other between three groups. We would like to conclude by suggesting that these data can be used in identifying the craniofacial skeletal patterns in early age and preventive methods can be used in cardiovascular risk factors. Additionally these results can be used by forensic anthropologists as well as fashion designers to correlate the ratio and craniofacial skeletal patterns.